Cancer cell-derived migrasomes harboring ATF6 promote breast cancer brain metastasis via endoplasmic reticulum stress-mediated disruption of the blood-brain barrier - Song Wang; Guohao Gu; Xinmiao Xian; Jun Li; Di Zhang; Jianran Guo; Anqi Zhang; Shen Chen; Dong Yan; Bingwu Yang; Meng An; Wei Zhang; et al. (Cancer Biology & Medicine, 2025)
Objective: Migrasomes, an emerging class of migration-facilitating membranous extracellular vesicles, remain largely uncharted in the intricate landscape of tumor metastasis. This study aimed to illuminate the roles and mechanisms underlying cancer cell-derived migrasomes in breast cancer brain metastasis (BCBM). Methods: Migrasomes were isolated and purified from BCBM cells (231-BR) and non-specific organotropic parental counterparts (MDA-MB-231), specifically designated as Mig-BCBM and Mig-BC, respectively. The role of Mig-BCBM in BCBM was investigated using an in vitro endothelial cell layer permeability model and a BCBM mouse model. The regulatory mechanism underlying Mig-BCBM was assessed using RT-qPCR, western blotting, immunofluorescence, ex vivo fluorescence imaging, and a series of rescue experiments. Results: Mig-BCBM potently augmented the permeability of vascular endothelial layers, which facilitated the efficient migration of 231-BR cells across endothelial barriers in vitro. The administration of Mig-BCBM significantly disrupted the blood-brain barrier (BBB) and accelerated BCBM progression in vivo, as evidenced in mouse models, compared to the Mig-BC and control groups. Mechanistically, Mig-BCBM harbored ATF6, a critical transducer of endoplasmic reticulum (ER) stress. Upon internalization into hCMEC/D3 cells, ATF6 elicited robust ER stress responses, culminating in downregulation of ZO-1 and VE-cadherin. Digital PCR analysis disclosed significant upregulation of ATF6 in serum migrasomes derived from BCBM patients compared to migrasomes from breast cancer patients and healthy individuals. Conclusions: This study uncovered a pivotal role of cancer cell-derived in BCBM by harnessing ATF6-mediated ER stress to disrupt the BBB and promote metastasis, suggesting novel diagnostic and therapeutic strategies targeting migrasomes and migrasome cargo.